Akuntansi Ilabulo: Studi Etnometodologi Islam - Thalib, Mohamad Anwar; Polapa, Asma; Rumampuk, Rismawati; Ma’luna, Sri Salni Safitri (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: Purpose: This study aims to construct labulo accounting practices based on local cultural values. Methodology/Approach: This study employs the Islamic framework from an Islamic ethno-methodology perspective. It uses a qualitative methodology that incorporates two data-gathering methods: structured interviews and passive participant observation. The participants in this study were chosen using purposive sampling techniques. The data analysis process consisted of five phases: amal, ilmu, iman, informasi wahyu, and ihsan. Results/Findings: The results indicate three ways in which Ilabulo traders practice accounting: profit accounting, loss accounting, and simple memory-based recording. These accounting practices are characterized by trustworthiness (amanah) and patience (kesabaran). Trustworthiness is reflected through sellers' actions, using their trading profits to support their families’ needs and children's education. The elders often advise the value of family responsibility through the expression (lumadu) "delo sipati lo malu'o tiloliyo kulu-kulu wala'iyo modudu'o," which means a sense of family responsibility. Patience is reflected in the actions of Ilabulo sellers when they experience losses, such as giving away their goods free to residents and continuing to trade despite facing losses. The elderly often advise on the value of patience through the expression (lumadu) "mopo'o tanggalo duhelo," which means being patient. Limitations: The limitation of this study lies in the informants, as it does not include information from Ilabulo customers. Contribution: This research contributes to introducing the concept of accounting practices by Ilabulo sellers based on local cultural values.